2019
DOI: 10.13181/mji.v28i3.3132
|View full text |Cite
|
Sign up to set email alerts
|

Double-J stents forgotten for four years: a case report

Abstract: Placement of double-J ureteral stents after endourologic procedures and some open urological surgeries are practical and safe. However, when neglected in situ, undesired problems may occur, leading to serious medical and legal issues. Complications from ureteral stents with protracted indwelling durations include urosepsis, renal failure, encrustation, and spontaneous fractures which may be retained or voided in the urine (stenturia). We report a 40-year-old woman of forgotten double-J ureteral stents, inserte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A study reported pain after SWL stent placement in 44% of patients along with dysuria, urgency and increased use of analgesia, which was subsided after stent removal 24 . A DJ stent, which was forgotten for four years in 40 years old female showed sepsis in ER, the severely encrusted DJ stent was then removed, and patient get symptom free 25 responsible to cause severe morbidity in pediatric population along with UTI, hematuria and encrustation of stent resulting in obstruction 26 . Stents strongly affect mental and physical health and cause pessimistic force on functional capability and work performed during the first post-operative weeks, patients with stent placement showed more consumption of pain relief medications orally than non-stented patients 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A study reported pain after SWL stent placement in 44% of patients along with dysuria, urgency and increased use of analgesia, which was subsided after stent removal 24 . A DJ stent, which was forgotten for four years in 40 years old female showed sepsis in ER, the severely encrusted DJ stent was then removed, and patient get symptom free 25 responsible to cause severe morbidity in pediatric population along with UTI, hematuria and encrustation of stent resulting in obstruction 26 . Stents strongly affect mental and physical health and cause pessimistic force on functional capability and work performed during the first post-operative weeks, patients with stent placement showed more consumption of pain relief medications orally than non-stented patients 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Timing for the stent removal depends on the patient's health history and the plan of care. Complications related to prolonged stent dwell-time include stent encrustation or the deposition of mineral crystals (uric acid or calcium oxalate) onto the surface and lumen of the stent 39,40…”
Section: Follow-up Carementioning
confidence: 99%
“…Stent encrustation can lead to further calculi formation causing tissue damage, obstruction, and pain. 41 Other complications include stent migration, most likely upward; infection from bacterial accumulation; and fragmentation of the stent due to deterioration 40…”
Section: Follow-up Carementioning
confidence: 99%